Case Book for Diploma ( General Dental Practice ) Part 1 - Chandraguptha, H.P (My University, 2011)
Dry socket; Pyogenic granuloma; Salivary mucocele; Fluorosis, Dental ; Fractured zygoma; Median diastema closure using light cured composite; Molar, An impacted third ; Siololith in the submandibular gland duct; Prosthetic treatment of an edentulous patient; Erythema multiforme; Malocclusion with an upper removable appliance, Correction of angle's class II division I ; Oral lichen planus; Dental management of a case of tricuspid valve defect with pulmonary stenosis; A patient with squamous cell carcinoma of the left buccal mucosa; Cyst, Radicular ; Trauma, Management of intruded left upper permanent central incisor due to ; Minor apthous stomatitis; Endodontic treatment of a non vital maxillary right lateral incisor and central incisor; Dento alveolar abscess related to mandibular molar teeth,A case of ; Correction of crossbite in relation to right and left upper permanent canine